Smart-Ubudiyah: A Strategy for Strengthening the Spirituality of Urban Communities in the 5.0 Era - Lathifatul Insaniyah, Anyes; Afif, Muhammad; Retno Putri, Dinda; Istibana; Danial Karomi, Ahmad; Ulil Absor, Moh. Naufal; Hafid, Nur (Simfoni Ilmu Cindekia, 2025)
Urban communities in densely populated areas often face spiritual challenges due to the fast pace of life and limited access to religious education. This condition results in low literacy in Islamic jurisprudence (fiqh) and results in worship that is less than compliant with Islamic law. This community service program aims to improve Islamic jurisprudence (fiqh) and establish a balance between worldly and spiritual life for urban communities in Kertosari and Karangrejo Villages, Banyuwangi. The methods used are participatory outreach and education through lectures, Q&A sessions, role-plays, and the use of information technology such as videos and infographics to simplify complex Islamic jurisprudence concepts. Mentoring involves studying the Taqrib book as a practical guide and the Bajuri book for deeper understanding, culminating in hands-on practice of ablution and prayer. The program results show a significant increase in community understanding of the requirements and pillars of worship. In addition to the spiritual impact of increased consistency in worship, this activity also strengthens social cohesion and solidarity among residents through collective activities such as completing the Quran and regular recitation. Overall, the contextual non-formal education approach has proven effective in improving the spiritual and social quality of society amidst the dynamics of urban life.